Surface-treated copper foil, copper-clad laminate, and method for manufacturing printed wiring board
Patent Information
- Application Number
- JP2023141527
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-08-31
AI Technical Summary
【0010】 本発明の実施形態によれば、一つの側面において、ソフトエッチングの際にアンダーカットの発生を抑制可能な表面処理銅箔及び銅張積層板を提供することができる。 また、本発明の実施形態によれば、別の側面において、アンダーカットが抑制された回路パターンを備えるプリント配線板の製造方法を提供することができる。
Smart Images

Figure 2025034865000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a surface-treated copper foil, a copper-clad laminate, and a printed wiring board. [Background technology]
[0002] Copper-clad laminates are manufactured by laminating copper foil and a base material composed of resin or the like. Copper-clad laminates are widely used in various applications such as flexible printed wiring boards. Flexible printed wiring boards are manufactured by etching the copper foil of a copper-clad laminate to form a circuit pattern (also called a "conductor pattern"), and mounting electronic components on the circuit pattern by connecting them with solder. Before mounting the electronic components, the circuit pattern is soft-etched to remove unnecessary materials from the surface of the copper foil and to roughen the surface of the copper foil.
[0003] The elements contained and / or the shape of the surface of the copper foil used in a copper-clad laminate are controlled so as to satisfy the required properties. For example, Patent Document 1 discloses a surface-treated copper foil that has excellent adhesion to resin, chemical resistance, and heat resistance, and is less likely to leave etching residues. The surface-treated copper foil includes a copper foil and a surface treatment layer (Zn-Ni-Mo layer) provided on at least one surface of the copper foil and having controlled Zn deposition amounts, Ni deposition amounts, and Mo deposition amounts. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019 / 188837 Summary of the Invention [Problem to be solved by the invention]
[0005] The surface-treated copper foil described in Patent Document 1 sometimes generates undercuts during soft etching, resulting in reduced reliability of the circuit pattern (eg, reduced adhesive strength between the substrate and the circuit pattern). The embodiments of the present invention have been made to solve the above problems, and in one aspect, an object of the present invention is to provide a surface-treated copper foil and a copper-clad laminate that can suppress the occurrence of undercuts during soft etching. Another object of the present invention is to provide a method for manufacturing a printed wiring board having a circuit pattern in which undercuts are suppressed. [Means for solving the problem]
[0006] As a result of extensive research into surface-treated copper foils, the present inventors have found that the above problems can be solved by forming a surface treatment layer containing Ni, Zn, and Cr on at least one side of a copper foil, and controlling the Zn deposition weight, the Cr deposition weight, and the ratio of the Cr deposition weight to the total of the Ni deposition weight, the Zn deposition weight, and the Cr deposition weight within a predetermined range, thereby completing an embodiment of the present invention.
[0007] That is, in one aspect, an embodiment of the present invention has a copper foil and a surface treatment layer formed on at least one surface of the copper foil, The surface treatment layer contains Ni, Zn and Cr, In the surface treatment layer, the amount of Zn attached is 100 to 500 μg / dm 2 The Cr deposition amount is 70 to 150 μg / dm 2 and the ratio of the Cr coating weight to the total of the Ni coating weight, the Zn coating weight, and the Cr coating weight is 18.0 to 50.0%.
[0008] In another aspect, an embodiment of the present invention relates to a copper-clad laminate comprising the above-mentioned surface-treated copper foil and a substrate provided on the surface treatment layer of the surface-treated copper foil.
[0009] Furthermore, in another aspect, an embodiment of the present invention relates to a method for producing a printed wiring board, which comprises etching the surface-treated copper foil of the copper-clad laminate to form a circuit pattern, and then performing soft etching. Effect of the Invention
[0010] According to one aspect of the present invention, a surface-treated copper foil and a copper-clad laminate capable of suppressing the occurrence of undercut during soft etching can be provided. According to another aspect of the present invention, there is provided a method for manufacturing a printed wiring board having a circuit pattern in which undercuts are suppressed. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a copper-clad laminate including a surface-treated copper foil according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a state in which a surface-treated copper foil of a copper-clad laminate including a surface-treated copper foil according to an embodiment of the present invention is etched to form a circuit pattern, and then soft-etched. [Diagram 3] FIG. 2 is a cross-sectional view showing an example of a state in which a surface-treated copper foil of a copper-clad laminate having a conventional surface-treated copper foil is etched to form a circuit pattern, and then soft-etched. [Figure 4] 1 is an example of an observed image of a circuit pattern in which an undercut has occurred. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Preferred embodiments of the present invention will be described in detail below, but the present invention should not be interpreted as being limited thereto, and various modifications and improvements can be made based on the knowledge of those skilled in the art without departing from the gist of the present invention. The multiple components disclosed in the following embodiments can be appropriately combined to form various inventions. For example, some components may be deleted from all the components shown in the following embodiments, or components of different embodiments may be appropriately combined.
[0013] The surface-treated copper foil according to the embodiment of the present invention has a copper foil and a surface treatment layer formed on at least one surface of the copper foil. The surface treatment layer contains Ni, Zn, and Cr, and the Zn coating amount in the surface treatment layer is 100 to 500 μg / dm 2 The Cr deposition amount is 70 to 150 μg / dm 2 and the ratio of the Cr coating weight to the total of the Ni coating weight, the Zn coating weight and the Cr coating weight is 18.0 to 50.0%. By adopting such a configuration, the surface-treated copper foil according to the embodiment of the present invention can suppress the occurrence of undercuts during soft etching.
[0014] The copper-clad laminate according to the embodiment of the present invention includes the above-mentioned surface-treated copper foil and a substrate provided on the surface treatment layer of the above-mentioned surface-treated copper foil. By adopting such a configuration, the copper-clad laminate according to the embodiment of the present invention can suppress the occurrence of undercuts when soft etching is performed after etching the surface-treated copper foil to form a circuit pattern.
[0015] FIG. 1 is a cross-sectional view showing an example of a copper-clad laminate including a surface-treated copper foil according to an embodiment of the present invention. 1, the surface-treated copper foil 1 has a copper foil 2 and a surface treatment layer 3 formed on at least one surface of the copper foil 2. The copper-clad laminate 10 includes the surface-treated copper foil 1 and a substrate 11 provided on the surface treatment layer 3 of the surface-treated copper foil 1.
[0016] FIG. 2 is a cross-sectional view showing an example of a state in which a surface-treated copper foil of a copper-clad laminate including a surface-treated copper foil according to an embodiment of the present invention is etched to form a circuit pattern, and then soft-etched. As shown in FIG. 2, in the circuit pattern 20 formed using a copper-clad laminate having a surface-treated copper foil according to an embodiment of the present invention, the surface treatment layer 3 in contact with the substrate 11 is not excessively eroded away compared to the copper foil 2, and the occurrence of undercuts can be suppressed.
[0017] FIG. 3 is a cross-sectional view showing an example of a state in which a surface-treated copper foil of a copper-clad laminate having a conventional surface-treated copper foil is soft-etched after the surface-treated copper foil is etched to form a circuit pattern. As shown in FIG. 3, in a circuit pattern 30 formed using a copper-clad laminate having a conventional surface-treated copper foil, the surface treatment layer 4 in contact with the substrate 11 is excessively eroded and removed compared to the copper foil 2, and undercuts 40 are likely to occur.
[0018] The surface treatment layer 3 used in the surface-treated copper foil 1 may be formed on only one side of the copper foil 2, or may be formed on both sides of the copper foil 2. When the surface treatment layer 3 is formed on both sides of the copper foil 2, the types of the surface treatment layers 3 may be the same or different.
[0019] The surface treatment layer 3 contains Ni, Zn and Cr. The surface treatment layer 3 may further contain Co, but does not necessarily need to contain Co. Among the various elements contained in the surface treatment layer 3, in order to suppress the occurrence of undercut during soft etching, the amount of Zn deposition is set to 100 to 500 μg / dm 2 , Cr deposition amount is 70 to 150 μg / dm 2It is also important to control the ratio of the Cr deposition weight to the total of the Ni deposition weight, Zn deposition weight, and Cr deposition weight (hereinafter, abbreviated as "Cr ratio") to 18.0 to 50.0%. By controlling the Zn deposition weight within this range, it is possible to impart properties such as heat resistance and chemical resistance to the surface treatment layer 3, and by controlling the Cr deposition weight within this range, it is also possible to impart an anti-rust effect. From the viewpoint of stably ensuring the effect of suppressing the occurrence of undercuts during soft etching, the Zn deposition weight is set to 151 to 394 μg / dm 2 It is preferable that the concentration is 151 to 331 μg / dm 2 From the same viewpoint, the Cr coating amount is more preferably 98 to 120 μg / dm 2 It is preferable that the concentration is 98 to 107 μg / dm 2 From the same viewpoint, the Cr content is preferably 20.0 to 40.0%, and more preferably 20.5 to 35.5%.
[0020] The amount of Ni attached in the surface treatment layer 3 is not particularly limited, but is preferably 10 to 100 μm / dm 2 It is preferable that the thickness is 27 to 72 μm / dm 2 By controlling the Ni deposition amount within such a range, the effect of suppressing the occurrence of undercut during soft etching can be enhanced.
[0021] In the soft etching solution used in soft etching, Ni is a component that is difficult to dissolve, whereas Zn is a component that is easily dissolved. Therefore, by controlling the balance between the Ni and Zn adhesion amounts in the surface treatment layer 3 within an appropriate range, the effect of suppressing the occurrence of undercuts during soft etching can be enhanced. From the viewpoint of obtaining this effect, the ratio of the Ni adhesion amount to the total of the Ni adhesion amount and the Zn adhesion amount in the surface treatment layer 3 is preferably 10.0 to 20.0%, and more preferably 15.2 to 18.2%. From the same viewpoint, the total of the Ni adhesion amount and the Zn adhesion amount in the surface treatment layer 3 is preferably 100 μg / dm 2 More than 500μg / dm 2It is preferable that the concentration is less than 178 to 466 μg / dm 2 It is more preferable that: The soft etching solution used for the soft etching is not particularly limited, and any solution known in the art may be used. A typical soft etching solution contains hydrogen peroxide and sulfuric acid as main components.
[0022] When the surface treatment layer 3 contains Co, the Co adhesion amount in the surface treatment layer 3 is 100 μg / dm 2 It is preferable that the concentration is less than 80 μg / dm 2 It is more preferable that the Co deposition amount is less than 0.1 μg / dm. By controlling the Co deposition amount within this range, it is possible to ensure the effect of suppressing the occurrence of undercut during soft etching. In addition, since Co is a magnetic metal, by controlling the Co deposition amount within this range, it is possible to obtain a surface-treated copper foil 1 that can be used to fabricate a printed wiring board with excellent high-frequency characteristics. The lower limit of the Co deposition amount is not particularly limited, but is typically 0.1 μg / dm. 2 , preferably 0.5 μg / dm 2 It is.
[0023] The Zn adhesion amount, Ni adhesion amount, and Co adhesion amount (if present) in the surface treatment layer 3 can be measured by dissolving the obtained surface-treated copper foil 1 in an aqueous nitric acid solution in which nitric acid and water are mixed in a volume ratio of 1:2, and performing ICP analysis. For the measurement, an inductively coupled plasma optical emission spectrometer (SPS3520UV, manufactured by Hitachi High-Tech Science Corporation) or an equivalent device can be used. The amount of Cr attached in the surface treatment layer 3 can be measured by boiling and dissolving the obtained surface-treated copper foil 1 in an aqueous hydrochloric acid solution in which the volume ratio of hydrochloric acid to water is 1:4, and performing quantitative analysis by atomic absorption spectrometry. For the measurement, an atomic absorption spectrophotometer (Agilent, 200 Series AA) or an equivalent device can be used.
[0024] The type of surface treatment layer 3 is not particularly limited as long as the amount of a specified element attached in the surface treatment layer 3 is controlled as described above, and a layer formed by various surface treatments known in the art can be used. Examples of the surface treatment layer 3 include a roughening treatment layer, a chemical resistance treatment layer, a heat resistance treatment layer, a chromate treatment layer, and a silane coupling treatment layer. These layers may be used alone or in combination of two or more. Among these layers, it is preferable that the surface treatment layer 3 contains a roughening treatment layer in order to improve adhesion to the substrate 11 (especially a resin substrate). Here, in this specification, the "roughened layer" refers to a layer formed by roughening treatment and contains roughening particles. In addition, in the roughening treatment, normal copper plating may be performed as a pretreatment, or normal copper plating may be performed as a finishing treatment to prevent the roughening particles from falling off, and the "roughened layer" in this specification includes layers formed by these pretreatments and finishing treatments.
[0025] When the surface treatment layer 3 contains one or more layers selected from the group consisting of a chemical resistance treatment layer, a heat resistance treatment layer, a chromate treatment layer, and a silane coupling treatment layer, it is preferable that these layers are provided on the roughening treatment layer.
[0026] The roughening particles are not particularly limited, but may be formed from any single element selected from the group consisting of copper, nickel, cobalt, phosphorus, tungsten, arsenic, molybdenum, chromium, and zinc, or an alloy containing one or more of these elements. The roughening particles may include primary roughening particles and secondary roughening particles. The secondary roughening particles preferably have a different chemical composition than the primary roughening particles. The primary roughening particles may be formed, for example, from copper or a copper alloy, especially copper. The secondary roughening particles may be formed, for example, from an alloy including copper, cobalt and nickel. A cover plating layer may be formed on at least a portion of the surface of the primary roughening particles. The cover plating layer is not particularly limited, but may be formed from copper, silver, gold, nickel, cobalt, zinc, etc. Among these, it is preferable that the cover plating layer is formed from copper.
[0027] The roughening treatment layer can be formed, for example, by performing a primary roughening treatment to form primary roughening particles, followed by cover plating to form a cover plating layer, and then a secondary roughening treatment to form secondary roughening particles. By performing the roughening treatment in this manner, it becomes easier to form the surface treatment layer 3 having the above-mentioned characteristics.
[0028] The roughening particle layer can be formed by electroplating. The conditions for the roughening treatment are not particularly limited, but typical conditions are as follows. The electroplating may be performed once or in multiple steps. (Roughening treatment conditions) Plating solution composition: 5-15g / L Cu, 40-100g / L sulfuric acid, 1-6ppm tungsten (derived from sodium tungstate dihydrate) Plating solution temperature: 20~50℃ Electroplating conditions: current density 30~90A / dm 2 , time 0.1 to 8 seconds (Conditions for cover plating) Plating solution composition: 10-30g / L Cu, 70-130g / L sulfuric acid Plating solution temperature: 30~60℃ Electroplating conditions: current density 4.8~15A / dm 2 , time 0.1 to 8 seconds
[0029] The chemical resistance layer and the heat resistance layer are not particularly limited and can be formed from materials known in the art. Since the chemical resistance layer can also function as a heat resistance layer, a single layer having both the functions of the chemical resistance layer and the heat resistance layer may be formed as the chemical resistance layer and the heat resistance layer. The chemical resistance layer and / or heat resistance layer may be a layer containing one or more elements (which may be in any form such as metal, alloy, oxide, nitride, sulfide, etc.) selected from the group consisting of nickel, zinc, tin, cobalt, molybdenum, copper, tungsten, phosphorus, arsenic, chromium, vanadium, titanium, aluminum, gold, silver, platinum group elements, iron, and tantalum. Among these, the chemical resistance layer and heat resistance layer are preferably Ni-Zn layers.
[0030] The chemical resistance treatment layer and the heat resistance treatment layer can be formed by electroplating. The conditions for electroplating are not particularly limited. Typical conditions for the chemical resistance treatment and the heat resistance treatment using a general electroplating device are as follows. Each electroplating may be performed once or multiple times. (Chemical resistance treatment and heat resistance treatment: Conditions for forming Ni-Zn layer) Plating solution composition: 1-30g / L Ni, 1-30g / L Zn Plating solution pH: 2~5 Plating solution temperature: 30~50℃ Electroplating conditions: current density 0.1~10A / dm 2 , time 0.1 to 5 seconds
[0031] The chromate treatment layer is not particularly limited and can be formed from materials known in the art. In this specification, the term "chromate-treated layer" refers to a layer formed from a liquid containing chromic anhydride, chromic acid, dichromate, or dichromate. The chromate-treated layer may be a layer containing one or more elements (which may be in any form such as metal, alloy, oxide, nitride, sulfide, etc.) selected from the group consisting of cobalt, iron, nickel, molybdenum, zinc, tantalum, copper, aluminum, phosphorus, tungsten, tin, arsenic, and titanium. Examples of chromate-treated layers include chromate-treated layers treated with an aqueous solution of chromic anhydride or potassium dichromate, and chromate-treated layers treated with a treatment liquid containing chromic anhydride or potassium dichromate and zinc.
[0032] The chromate treatment layer can be formed by a known method such as immersion chromate treatment or electrolytic chromate treatment. The conditions of the chromate treatment are not particularly limited. Typical conditions of general chromate treatment are as follows. The chromate treatment may be performed once or in multiple steps. Chromate solution composition: 1-10g / L K2Cr2O7, 0.01-10g / L Zn Chromate solution pH: 2~5 Chromate solution temperature: 30~55℃ Electrolysis conditions: current density 0.1~10A / dm 2 , time 0.1 to 5 seconds (in the case of electrolytic chromate treatment)
[0033] The silane coupling treatment layer is not particularly limited, and can be formed from a material known in the art. In this specification, the term "silane coupling treatment layer" refers to a layer formed from a silane coupling agent. The silane coupling agent is not particularly limited, and can be one known in the art. Examples of the silane coupling agent include amino-based silane coupling agents, epoxy-based silane coupling agents, mercapto-based silane coupling agents, methacryloxy-based silane coupling agents, vinyl-based silane coupling agents, imidazole-based silane coupling agents, and triazine-based silane coupling agents. Among them, amino-based silane coupling agents and epoxy-based silane coupling agents are preferred. The silane coupling agents may be used alone or in combination of two or more. A typical method for forming the silane coupling treatment layer is to apply a 1 to 3% by volume aqueous solution of the above-mentioned silane coupling agent and dry it to form the silane coupling treatment layer.
[0034] The copper foil 2 used in the surface-treated copper foil 1 is not particularly limited, and may be either an electrolytic copper foil or a rolled copper foil. Electrolytic copper foil is produced, for example, by electrolytically depositing copper from a copper sulfate plating bath onto a drum made of titanium or stainless steel. Electrolytic copper foil has a flat S-side (shine side) formed on the drum side and an M-side (matte side) formed on the opposite side to the S-side.
[0035] The material of the copper foil 2 is not particularly limited. When the copper foil 2 is a rolled copper foil, high purity copper such as tough pitch copper (JIS H3100 alloy number C1100) and oxygen-free copper (JIS H3100 alloy number C1020 or JIS H3510 alloy number C1011) that are usually used as circuit patterns of printed wiring boards can be used. In addition, copper alloys such as copper containing Sn, copper containing Ag, copper alloys containing Cr, Zr, Mg, etc., and Corson copper alloys containing Ni and Si can also be used. In this specification, the term "copper foil 2" is a concept that includes copper alloy foil.
[0036] The thickness of the copper foil 2 is not particularly limited, but can be, for example, 1 to 1000 μm, 1 to 500 μm, 1 to 300 μm, 3 to 100 μm, 5 to 70 μm, 6 to 35 μm, or 9 to 18 μm.
[0037] The surface-treated copper foil 1 composed of the copper foil 2 and the surface treatment layer 3 as described above can be produced according to a method known in the art. Here, the Ni deposition amount, Zn deposition amount, Cr deposition amount and Co deposition amount (if present) in the surface treatment layer 3 can be controlled by adjusting the formation conditions of the surface treatment layer 3. The formation conditions include, for example, the magnitude of the current value, the surface treatment time, the concentration of each metal ion in the bath, the temperature and pH of the bath, etc.
[0038] As described above, the copper clad laminate 10 according to the embodiment of the present invention includes the surface-treated copper foil 1 and the substrate 11 provided on the surface treatment layer 3 of the surface-treated copper foil 1. This copper-clad laminate 10 can be produced by adhering a substrate 11 to the surface-treated layer 3 of the surface-treated copper foil 1 . The substrate 11 is not particularly limited, and any substrate known in the art can be used, but is preferably a resin substrate. Examples of the resin substrate include substrates made of a paper substrate with phenolic resin, a paper substrate with epoxy resin, a synthetic fiber cloth substrate with epoxy resin, a glass cloth / paper composite substrate with epoxy resin, a glass cloth / glass nonwoven fabric composite substrate with epoxy resin, a glass cloth substrate with epoxy resin, a polyester film, a polyimide resin, a liquid crystal polymer, a fluororesin, etc. Among these, the resin substrate is preferably a substrate made of polyimide resin.
[0039] The method for bonding the surface-treated copper foil 1 and the base material 11 is not particularly limited and can be performed according to a method known in the art. For example, the surface-treated copper foil 1 and the base material 11 may be laminated and thermocompression bonded. The copper clad laminate 10 thus produced can be used in the manufacture of printed wiring boards.
[0040] The copper-clad laminate 10 according to an embodiment of the present invention uses the above-mentioned surface-treated copper foil 1, and therefore, after etching the surface-treated copper foil 1 to form the circuit pattern 20, the occurrence of undercuts can be suppressed when soft etching is performed.
[0041] The method for manufacturing a printed wiring board according to the embodiment of the present invention is performed by etching the surface-treated copper foil 1 of the copper-clad laminate 10 to form a circuit pattern 20, and then soft etching. The method for forming the circuit pattern 20 is not particularly limited, and known methods such as a subtractive method and a semi-additive method can be used. Among them, the subtractive method is preferable as the method for forming the circuit pattern 20.
[0042] When a printed wiring board is manufactured by the subtractive method, it is preferably carried out as follows. First, a resist is applied to the surface of the surface-treated copper foil 1 of the copper-clad laminate 10, and a predetermined resist pattern is formed by exposing and developing it. Next, the surface-treated copper foil 1 in the portion where the resist pattern is not formed (i.e., the unnecessary portion) is removed by etching to form a circuit pattern 20. Finally, the resist pattern on the surface-treated copper foil 1 is removed, and soft etching is performed. The conditions for this subtractive method are not particularly limited, and the method can be carried out according to the conditions known in the art.
[0043] The method for manufacturing a printed wiring board according to an embodiment of the present invention uses the above-mentioned copper-clad laminate 10, and therefore it is possible to form a circuit pattern 20 in which undercuts are suppressed, and in particular, the reliability of the circuit pattern 20 (e.g., the adhesion strength between the substrate 11 and the circuit pattern 20) is good. EXAMPLES
[0044] The embodiments of the present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0045] Example 1 A rolled copper foil (HG foil manufactured by JX Metals Corporation) with a thickness of 12 μm was prepared. Both sides of the copper foil were degreased and pickled, and then a roughening treatment layer, a heat-resistant and chemical-resistant treatment layer (Ni-Zn layer), a chromate treatment layer, and a silane coupling treatment layer were successively formed as surface treatment layers on one side (hereinafter referred to as the "first side") to obtain a surface-treated copper foil. The conditions for forming each treatment layer were as follows.
[0046] (1) Roughened layer / first surface <Conditions for forming roughening particles> Plating solution composition: 12g / L Cu, 50g / L sulfuric acid, 5ppm tungsten (derived from sodium tungstate dihydrate) Plating solution temperature: 27℃ Number of plating processes: 2 Electroplating conditions: Current density 49.8 A / dm 2 , time 0.81 seconds <Formation conditions of the coating layer> Coating solution composition: 20 g / L of Cu, 100 g / L of sulfuric acid Coating solution temperature: 50 °C Number of coating treatments: 2 times Electroplating conditions: Current density 11.9 A / dm 2 , time 1.15 seconds
[0047] (2) Heat-resistant and chemical-resistant treatment layer / First surface <Formation conditions of the Ni-Zn layer> Coating solution composition: 23.5 g / L of Ni, 4.5 g / L of Zn Coating solution pH: 3.6 Coating solution temperature: 40 °C Electroplating conditions: Current density 0.70 A / dm 2 , time 0.59 seconds Number of coating treatments: 1 time
[0048] (3) Chromate treatment layer / First surface <Formation conditions of the electrolytic chromate treatment layer> Chromate solution composition: 3 g / L of K2Cr2O7, 0.33 g / L of Zn Chromate solution pH: 3.65 Chromate solution temperature: 55 °C Electrolysis conditions: Current density 1.9 A / dm 2 , time 0.59 seconds Number of chromate treatments: 2 times
[0049] (4) Silane coupling treatment layer / First surface A 1.2% by volume aqueous solution of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane was applied and dried to form a silane coupling treatment layer.
[0050] (Example 2) In the formation conditions of the heat-resistant and chemical-resistant treatment layer (Ni-Zn layer) / First surface, the electroplating conditions were a current density of 1.5 A / dm 2, A surface-treated copper foil was obtained under the same conditions as in Example 1, except that the time was changed to 0.59 seconds.
[0051] (Example 3) In the formation conditions of the heat-resistant and chemical-resistant treatment layer (Ni-Zn layer) / first surface, the electroplating conditions were changed to a current density of 1.9 A / dm 2 , A surface-treated copper foil was obtained under the same conditions as in Example 1, except that the time was changed to 0.59 seconds.
[0052] (Example 4) In the formation conditions of the heat-resistant and chemical-resistant treatment layer (Ni-Zn layer) / first surface, the electroplating conditions were changed to a current density of 2.2 A / dm 2 , A surface-treated copper foil was obtained under the same conditions as in Example 1, except that the time was changed to 0.59 seconds.
[0053] (Comparative Example 1) (1) Roughening treatment layer / first surface <Formation conditions of roughening particles> Plating solution composition: 11 g / L of Cu, 50 g / L of sulfuric acid Plating solution temperature: 27 °C Number of plating treatments: 2 times Electroplating conditions: Current density 41.3 A / dm 2 , Time 0.68 seconds <Formation conditions of overlay plating layer> Plating solution composition: 20 g / L of Cu, 100 g / L of sulfuric acid Plating solution temperature: 50 °C Number of plating treatments: 2 times Electroplating conditions: Current density 8.2 A / dm 2 , Time 0.77 seconds
[0054] (2) Heat-resistant and chemical-resistant treatment layer / first surface <Formation conditions of Ni-Zn layer> Plating solution composition: 23.5 g / L of Ni, 4.5 g / L of Zn Plating solution pH: 3.6 Plating solution temperature: 40 °C Electroplating conditions: Current density 3.42 A / dm 2 , Time 0.39 seconds Number of plating processes: 1
[0055] (3) Chromate layer / first surface <Conditions for forming electrolytic chromate treatment layer> Chromate solution composition: 3g / L K2Cr2O7, 0.33g / L Zn Chromate solution pH: 3.65 Chromate solution temperature: 55℃ Electrolysis conditions: current density 2.7A / dm 2 , time 0.39 seconds Chromate treatment times: 2 times
[0056] (4) Silane coupling treatment layer / first surface A 1.2% by volume aqueous solution of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane was applied and dried to form a silane coupling treatment layer.
[0057] The surface-treated copper foils obtained in Examples 1 to 4 and Comparative Example 1 were evaluated as follows. <Amount of each element attached to the surface treatment layer (first surface)> The Zn and Ni adhesion amounts in the surface treatment layer were measured by dissolving the resulting surface-treated copper foil in an aqueous nitric acid solution with a volume ratio of nitric acid:water = 1:2 and then performing ICP analysis using an inductively coupled plasma optical emission spectrometer (Hitachi High-Tech Science Corporation, SPS3520UV). The amount of Cr attached in the surface treatment layer was measured by boiling and dissolving the surface-treated copper foil in a hydrochloric acid solution with a volume ratio of hydrochloric acid:water = 1:4, and performing quantitative analysis by atomic absorption spectrometry using an atomic absorption spectrophotometer (Agilent, 200 Series AA) for the measurement. The deposition weights of Zn, Ni and Cr are calculated based on the unit area (dm 2 The values are expressed as the attached mass (μg) of Zn, Ni and Cr per unit area. In addition, based on the obtained deposition amounts of elements, the ratio of the Ni deposition amount to the sum of the Ni deposition amount and the Zn deposition amount (referred to as the "Ni rate"), and the ratio of the Cr deposition amount to the sum of the Ni deposition amount, the Zn deposition amount, and the Cr deposition amount (referred to as the "Cr rate") were calculated.
[0058] <Undercut width> After the surface-treated copper foil (first surface) and a 25 μm-thick polyimide film (Pixio (registered trademark) manufactured by Kaneka Corporation) were bonded together, they were held at 360° C. for 30 minutes for thermocompression bonding. All of these thermocompression bonding processes were carried out at 2.5 kPa. Next, a circuit pattern was formed so that the width was 200 μm using an etching solution. Next, soft etching was carried out for 1 minute on this circuit pattern using a soft etching solution (Clean Etch CPE-750 manufactured by Mitsubishi Gas Chemical Co., Ltd.) mainly composed of hydrogen peroxide and sulfuric acid. Then, the undercut after soft etching was observed from the back side of the polyimide film with an optical microscope. Here, an example of an observation image of a circuit pattern in which an undercut occurred is shown in FIG. 4. Since the polyimide film is thin and transparent, it is possible to observe the undercut and measure the undercut widths W1 and W2 through the polyimide film. The undercut widths W1 and W2 were measured at three arbitrarily selected points, and the average value of these measurements was taken as the result of the undercut width. The results of the above characteristic evaluations are shown in Table 1.
[0059] [Table 1]
[0060] As shown in Table 1, the surface treatment layer contains Ni, Zn, and Cr, and the amount of Zn attached in the surface treatment layer is 100 to 500 μg / dm 2 The Cr deposition amount is 70 to 150 μg / dm 2 The surface-treated copper foils of Examples 1 to 4, in which the Cr ratio was 18.0 to 50.0%, had smaller undercut widths than those of Comparative Example 1, in which the Cr coating amount and Cr ratio of the surface treatment layer were outside the above ranges.
[0061] As can be seen from the above results, according to the embodiment of the present invention, it is possible to provide a surface-treated copper foil and a copper-clad laminate capable of suppressing the occurrence of undercuts when forming a circuit pattern by soft etching. Also, according to the embodiment of the present invention, it is possible to provide a method for manufacturing a printed wiring board having a circuit pattern in which undercuts are suppressed.
[0062] Therefore, the embodiment of the present invention can have the following aspects. [1] A copper foil and a surface treatment layer formed on at least one surface of the copper foil, The surface treatment layer contains Ni, Zn and Cr, In the surface treatment layer, the amount of Zn attached is 100 to 500 μg / dm 2 The Cr deposition amount is 70 to 150 μg / dm 2 and the ratio of the Cr coating weight to the total of the Ni coating weight, the Zn coating weight, and the Cr coating weight is 18.0 to 50.0%. [2] The surface treatment layer further contains Co, In the surface treatment layer, the Co deposition amount is 100 μg / dm 2 The surface-treated copper foil according to [1], [3] The surface-treated copper foil according to [1], wherein the surface treatment layer does not contain Co. [4] The amount of Zn attached is 151 to 394 μg / dm 2 The surface-treated copper foil according to any one of [1] to [3], [5] The amount of Zn attached is 151 to 331 μg / dm 2 The surface-treated copper foil according to [4], [6] The Cr coating amount is 98 to 120 μg / dm 2 The surface-treated copper foil according to any one of [1] to [5], [7] The Cr coating amount is 98 to 107 μg / dm 2 The surface-treated copper foil according to [6], [8] The Ni coating amount is 10 to 100 μg / dm 2 The surface-treated copper foil according to any one of [1] to [7], [9] The Ni coating amount is 27 to 72 μg / dm 2 The surface-treated copper foil according to [8],
[10] The surface-treated copper foil according to any one of [1] to [9], wherein a ratio of the Cr coating weight to the total of the Ni coating weight, the Zn coating weight, and the Cr coating weight is 20.0 to 40.0%.
[11] The surface-treated copper foil according to
[10] , wherein a ratio of the Cr coating weight to the total of the Ni coating weight, the Zn coating weight, and the Cr coating weight is 20.5 to 35.5%.
[12] The surface-treated copper foil according to any one of [1] to
[11] , wherein a ratio of the Ni coating weight to the total of the Ni coating weight and the Zn coating weight is 10.0 to 20.0%.
[13] The surface-treated copper foil according to
[12] , wherein a ratio of the Ni coating weight to the total of the Ni coating weight and the Zn coating weight is 15.2 to 18.2%.
[14] The total of the Ni coating amount and the Zn coating amount is 100 μg / dm 2 More than 500μg / dm 2 The surface-treated copper foil according to any one of [1] to
[13] , wherein
[15] The total of the Ni coating amount and the Zn coating amount is 178 to 466 μg / dm 2 The surface-treated copper foil according to
[14] ,
[16] The surface-treated copper foil according to any one of [1] to
[15] , wherein the surface treatment layer contains a roughening treatment layer.
[17] A copper-clad laminate comprising the surface-treated copper foil according to any one of [1] to
[16] and a substrate provided on the surface treatment layer of the surface-treated copper foil.
[18] A method for producing a printed wiring board, comprising etching the surface-treated copper foil of the copper-clad laminate according to
[17] to form a circuit pattern, and then soft-etching the resulting product. [Explanation of symbols]
[0063] 1. Surface-treated copper foil 2 Copper foil 3,4 Surface treatment layer 10 Copper-clad laminate 11 Base material 20,30 Circuit Pattern 40 Undercut
Claims
1. A copper foil and a surface treatment layer formed on at least one surface of the copper foil, The surface treatment layer contains Ni, Zn and Cr, In the surface treatment layer, the amount of Zn attached is 100 to 500 μg / dm 2 The Cr deposition amount is 70 to 150 μg / dm 2 and a ratio of the Cr coating weight to the total of the Ni coating weight, the Zn coating weight, and the Cr coating weight is 18.0 to 50.0%.
2. The surface treatment layer further contains Co, In the surface treatment layer, the amount of Co attached is 100 μg / dm 2 The surface-treated copper foil according to claim 1, wherein:
3. The surface-treated copper foil according to claim 1 , wherein the surface treatment layer does not contain Co.
4. The amount of Zn attached is 151 to 394 μg / dm 2 The surface-treated copper foil according to claim 1 .
5. The amount of Zn attached is 151 to 331 μg / dm 2 The surface-treated copper foil according to claim 4 .
6. The Cr deposition amount is 98 to 120 μg / dm 2 The surface-treated copper foil according to claim 1 .
7. The Cr deposition amount is 98 to 107 μg / dm 2 The surface-treated copper foil according to claim 6 .
8. The amount of Ni attached is 10 to 100 μg / dm 2 The surface-treated copper foil according to claim 1 .
9. The Ni deposition amount is 27 to 72 μg / dm 2 The surface-treated copper foil according to claim 8 .
10. 2. The surface-treated copper foil according to claim 1, wherein a ratio of the Cr coating weight to the total of the Ni coating weight, the Zn coating weight, and the Cr coating weight is 20.0 to 40.0%.
11. The surface-treated copper foil according to claim 10, wherein a ratio of the Cr coating weight to the total of the Ni coating weight, the Zn coating weight, and the Cr coating weight is 20.5 to 35.5%.
12. 2. The surface-treated copper foil according to claim 1, wherein the ratio of the Ni deposition weight to the total of the Ni deposition weight and the Zn deposition weight is 10.0 to 20.0%.
13. The surface-treated copper foil according to claim 12, wherein a ratio of the Ni coating weight to the total of the Ni coating weight and the Zn coating weight is 15.2 to 18.2%.
14. The total of the Ni deposition amount and the Zn deposition amount is 100 μg / dm 2 500 μg / dm or more 2 The surface-treated copper foil of claim 1 , wherein the surface-treated copper foil has a viscosity of less than 1000 nm.
15. The total of the Ni deposition amount and the Zn deposition amount is 178 to 466 μg / dm 2 The surface-treated copper foil according to claim 14 .
16. The surface-treated copper foil according to any one of claims 1 to 15, wherein the surface treatment layer contains a roughening treatment layer.
17. A copper-clad laminate comprising the surface-treated copper foil according to any one of claims 1 to 15 and a substrate provided on the surface treatment layer of the surface-treated copper foil.
18. A method for producing a printed wiring board, comprising etching the surface-treated copper foil of the copper-clad laminate according to claim 17 to form a circuit pattern, and then soft-etching the surface-treated copper foil.
Citation Information
Patent Citations
Rolled copper foil for printed wiring board, and manufacturing method thereof
JP2009188369A
Surface-treated copper foil, laminate and printed wiring board
JP2019019414A
Surface-treated copper foil for high-frequency circuit, and method for producing the same
JP2021147701A
Rolled copper foil or electrolytic copper foil for electronic circuit, and method for forming electronic circuit using the rolled copper foil or electrolytic copper foil
WO2010074072A1
Copper foil for printed circuit
WO2012132577A1